PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO TUTORIAL TATA RIAS WAJAH PANGGUNG BERBASIS SIBI DI KARYA MULIA SURABAYA - Shafiyyah, Salma; Lutfiati, Dewi; Fernanda, M.A. Hanny Ferry; Nia Kussianti (Jurnal Tata Rias, 2025)
Practical learning of stage makeup for deaf students often faces obstacles due to the lack of accessible media that supports visual communication, particularly those utilizing the Indonesian Sign System (SIBI). Therefore, this study aimed to: (1) develop a SIBI-based video tutorial as an instructional medium for stage makeup competence; (2) assess the feasibility of the developed media; (3) measure students’ psychomotor learning outcomes after using the media; and (4) evaluate student responses to the SIBI-based video tutorial at SMALB-B Karya Mulia Surabaya. This research employed the 4D development model (Define, Design, Develop, Disseminate). The results showed that: (1) the media was successfully developed in the form of a ±7-minute video tutorial that integrated practical demonstrations, text, audio, and SIBI in a systematic manner; (2) the feasibility validation reached an average score of 88%, with media experts rating it at 92% (highly feasible), and both material and language experts giving 86% (feasible); (3) students' psychomotor learning outcomes improved, with the average knowledge test score increasing from 44.29 (pre-test) to 79.29 (post-test), and all students achieving psychomotor scores above the Minimum Mastery Criteria (KKTP), with an average of 83.8; and (4) student responses to the media were highly positive, with an average score of 4.35. These findings indicate that the SIBI-based video tutorial is both effective and feasible for use in practical learning among deaf students. Keywords: video tutorial, stage makeup, sign language, SIBI, deaf students.